(untitled) (International Journal of Engineering and Computer Science, 2017)
An adaptive-update-rate target-tracking algorithm is indeed a developed version of constant-update-rate tracking algorithms. The update rate is closely related with the level of target maneuvering and the required quality of tracking performance— the shorter the time intervals between two successive updates, the better the radar resources are made use of. Considering the needs of the phased-array radar system and multi-function tracking, we here propose an algorithm which makes a better use of radar resources; therefore, many targets can be tracked with an improved accuracy, and more regions can be detected. The proposed algorithm is based upon the adaptive interactive tracking algorithm (AIMM); the revisit time has been calculated using Van Keuk method, and then the fast AIMM has been amended such that the tracking error is no more than that in Van Keuk method. Our proposed algorithm which has a revisit time different than Van Keuk’s results in 62% saving of the radar resources.